Logotherapy Counseling to Improve Acceptance of Broken Home Child - Erlangga, Erwin (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2017)
This study aims to increase the enrollment of children of a broken home that life has meaning. Subjects are 100 children in Demak whose families experiencing divorce. Research themes include three things: individual counseling, engineering logotherapy, reception, and a child of a broken home. Data obtained based on interviews, observation, and psychological scale showed that of the 100 children of a broken home has a low acceptance that individual counseling with logotherapy techniques were considered appropriate to increase the enrollment of children of a broken home. Factors - factors that affect the acceptance of a child of a broken home is self-blame, anger and did not have a purpose in life again. In addition the environment is also a significant effect on the enrollment of children of a broken home. Environmental labeling of families experiencing divorce as a family that failed so that children are increasingly stressed with the stamp of the community. Based on the field test results, the level of acceptance of the child of a broken home increases after the individual is given counseling services with logotherapy techniques. Indicated by changes in the level of acceptance of children of a broken home before being given treatment (initial evaluation) and after (final evaluation) of 130 points. The results of effectiveness test statistic t test calculations also showed 0,010 <0.05.It was concluded that counseling individuals with logotherapy effective technique to increase the enrollment of children of a broken home